The influence of neighborhood built environment on school-age children’s outdoor leisure activities and obesity: a case study of Shanghai central city in China - Tan, Weifan; Lu, Xiaocong; Xiao, Tingting (Frontiers in Public Health, 2023)
Objective The aim of this study was to examine the influencing pathways of the neighborhood built environment on children’s outdoor leisure activities and obesity. Methods A total of 378 elementary school students from 10 schools in central Shanghai were selected by a convenient sampling method for questionnaire survey and accelerometer tracking. Results 1) The neighborhood built environment could affect children’s obesity not only through direct effect (β = 0.15, p < 0.05), but also through the mediating effect of outdoor leisure activities (β = 0.19, p < 0.05). 2) For boys, the neighborhood built environment could affect children’s obesity not only through direct effect (β = 0.17, p < 0.05), but also through the mediating effect of outdoor leisure activities (β = 0.26, p < 0.05). For girls, the neighborhood built environment could affect children’s obesity only through the mediating effect of outdoor leisure activities (β = 0.13, p < 0.05). Conclusion The neighborhood built environment and outdoor leisure activities are important influencing factors in children’s obesity. The neighborhood built environment and outdoor leisure activities could have direct and indirect effects on children’s obesity, while there are gender differences in the influencing pathways of the neighborhood built environment on children’s obesity. This study suggests that improving the neighborhood built environment and promoting outdoor leisure activities in children have important value for influencing children’s obesity.